LncRNA‐ROR alleviates hypoxia‐triggered damages by downregulating miR‐145 in rat cardiomyocytes H9c2 cells. Issue 12 (12th June 2019) - Wang, Pengxi; Yuan, Yanran
Abstract: Chronic hypoxic heart disease (CHD) is a common clinical type of congenital heart disease. Long noncoding RNA regulator of reprogramming (lncRNA‐ROR) exerts an important regulating effect in cardiovascular diseases. In our study, we explored the effect of lncRNA‐ROR and the possible mechanisms against hypoxia‐caused apoptosis in H9c2 cells. H9c2 cells were exposed to hypoxia (1% O2 ) to construct the in vitro model of CHD. The level of lncRNA‐ROR and microRNA (miRNA/miR)‐145 was detected. To upregulate the level of lncRNA‐ROR and miR‐145, transfection was carried out. Western blot assay was performed to quantified protein expression. The interaction of lncRNA‐ROR with miR‐145 was verified by RIP and Dual‐luciferase reporter assays. The expression of p53 and Bax was largely elevated and Bcl‐2 was suppressed by hypoxia induction. We found that lncRNA‐ROR was elevated by hypoxia. LncRNA‐ROR overexpression was able to relieve the damages of H9c2 cells induced by hypoxia through rescuing viability, suppressing apoptosis, and blocking Cytochrome c release. miR‐145 was suppressed by overexpressed lncRNA‐ROR and the combination of miR‐145 mimic was able to abolish the protective effect of lncRNA‐ROR. Moreover, we found that lncRNA‐ROR activated Ras/Raf/MEK/ERK and PI3K/AKT transduction cascades by suppressing miR‐145. Besides, lncRNA‐ROR directly targeted miR‐145 and negatively modulated the level of miR‐145. Our present study revealed that lncRNA‐ROR protected H9c2 cells against hypoxia‐caused damages by regulation of miR‐145 through activating Ras/Raf/MEK/ERK and PI3K/AKT. Abstract : Our present study revealed that lncRNA‐ROR protected H9c2 cells against hypoxia‐caused damages by regulation of miR‐145 through activating Ras/Raf/MEK/ERK and PI3K/AKT.